1950
DOI: 10.1161/01.cir.1.2.241
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Auricular Arrhythmias

Abstract: The four auricular arrhythmias, premature systoles, paroxysmal tachycardia, flutter, and fibrillation, have been investigated in over 200 dogs by three methods: (1) high speed cinematography, (2) cathode-ray oscillography, and (3) multiple-channel electrocardiography. The hitherto unexplored body of the left auricle has been surgically exposed and thoroughly studied. Results indicate that all four arrhythmias are of unitary origin and may occur from one ectopic focus. The resulting arrhythmia depends largely u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0

Year Published

1950
1950
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 2 publications
1
43
0
Order By: Relevance
“…Continued regeneration of new wave breaks at multiple locations is the mechanism that sustains VF. In contrast, the focal-source hypothesis 16 states that a rapidly activating focal source drives the ventricle into fibrillation through fibrillatory conduction. This rapidly activating focal source could be a mother rotor 17 associated with a single PS.…”
Section: Possible Mechanisms Of Cardiac Fibrillationmentioning
confidence: 99%
“…Continued regeneration of new wave breaks at multiple locations is the mechanism that sustains VF. In contrast, the focal-source hypothesis 16 states that a rapidly activating focal source drives the ventricle into fibrillation through fibrillatory conduction. This rapidly activating focal source could be a mother rotor 17 associated with a single PS.…”
Section: Possible Mechanisms Of Cardiac Fibrillationmentioning
confidence: 99%
“…In some of the experiments there was a change of only 8 per cent and in another a 39 per cent change in rate was necessary before reversion to sinus rhythm occurred. Table 1 summarizes the data obtained in the 32 experiments considered in this report.…”
mentioning
confidence: 99%
“…In fact, Prinzmetal et al (1952) tentatively suggested a unitary nature of the two arrhythmias. However, there are serious objections to such a view.…”
Section: Discussionmentioning
confidence: 99%
“…It is equally well known that different types of atrial arrhythmias can be produced in animals by local application of various drugs to the epicardial surface of the heart (Scherf, 1944(Scherf, , 1947Kisch, 1944;Scherf & Chick, 1951;Prinzmetal, Corday, Brill, Oblath & Kruger, 1952;Scherf, Blumenfeld, Taner & Yildiz, 1960), but it has never been shown that any of these resemble paroxysmal atrial tachycardia in man by the crucial test of being consistently suppressible by means of carotid sinus stimulation. It has now been found that the arrhythmia produced by subepicardial injection of ouabain is regularly susceptible to carotid sinus stimulation.…”
mentioning
confidence: 99%